THE DELICATE DANCE: DILEMMAS OF THE IGBO APPRENTICESHIP MODEL IN NIGERIA - SAMUEL ALEGWU OMANCHI; MARY OMATEI OMALE (International Studies Journal)
The Igbo apprenticeship model, deeply embedded in Igbo culture and a driver of economic success, faces contemporary challenges in Nigeria. This paper explores the key dilemmas of the model, including the tension between modernization and traditional values, limited social and economic mobility, gender and inclusion issues, and concerns about sustainability and relevance. To achieve this, anthropological and historical methodologies were used to generate data, while the qualitative method was used for the analysis. We argue that navigating these dilemmas requires a delicate balance between preserving the model's strengths and adapting to modern realities. Potential solutions include skill development programs, microfinance initiatives, formalization and regulation, promoting inclusivity, and government collaboration. By addressing these challenges and embracing ongoing adaptation, the Igbo apprenticeship model can continue to be a powerful tool for entrepreneurship, community development, and cultural preservation in Nigeria.